The effect of the COVID-19 lockdown on hand trauma surgery utilization - Atia, Fady (Bone Jt Open, 2020)
AIMS: The aim of this study was to evaluate the need for hand trauma services during the COVID-19 pandemic lockdown, specifically related to surgical requirements. This will provide useful information for planning and resource allocation in the event of any further lockdown. METHODS: A prospective analsysis of all patients attending our hand trauma unit throughout the UK COVID-19 lockdown period (24 March to 10 May 2020) was carried out. Prospectively collected departmental data from the same period in 2019 was obtained and reviewed for comparison. The number of patients attending clinic, undergoing surgery, the type of surgical procedure, and rate of surgery was compared. RESULTS: In all, 463 patients attended hand trauma services during the lockdown period compared to 793 in 2019 (32% reduction); 190 surgical procedures were carried out during lockdown compared to 236 in 2019 (20% reduction). Intervention rate was higher during the lockdown period (41% compared to 30%). There was no difference in the type of cases. In the first half of lockdown, 47% fewer procedures were performed than in 2019, but in the second half of lockdown 13% more procedures were carried out than the same period in 2019. CONCLUSION: Requirements for hand trauma surgery remain high during a pandemic lockdown. Attendances and surgical requirements can be expected to steadily return to normal levels during a prolonged lockdown period. Throughout any future lockdown period adequate surgical provision must be maintained for patients with hand injuries. Cite this article: Bone Joint Open 2020;1-10:639–643.